REPRESENTASI SIFAT-SIFAT TELADAN NABI MUHAMMAD MELALUI PENOKOHAN KIAI MOEKTI DALAM NOVEL SEBUAH SURAU KARYA ARTIE AHMAD - Nugraha, Shafwan; Kalsum, Rahma Sari; Supriatna, Agus (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2023)
The research undertakes a qualitative examination of the representation of Prophet Muhammad's qualities as an exemplary figure for the Islamic community through the characterization of one of the novel's protagonists titled